Centers on center manifolds in the Lu system - Mahdi, Adam; Pessoa, Claudio; Shafer, Douglas S. (Elsevier B.V., 2011)
We confirm a conjecture of Mello and Coelho [Phys. Lett. A 373 (2009) 1116] concerning the existence of centers on local center manifolds at equilibria of the Lu system of differential equations on R(3). Our proof shows that the local center manifolds are algebraic ruled surfaces, and are unique. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Center problem; Center manifold; Integrability